STUDI TENTANG PARTISIPASI JUNIOR CHAMBER INTERNATIONAL DALAM PEMENUHAN HAK-HAK PENYANDANG DISABILITAS DI KOTA SAMARINDA - Henny Sulistiawati (Magister Administrasi Publik FISIP Universitas Mulawarman, 2020)
This research aims to find out, describe, and analyze Junior Chamber International's participation and supporting factors and obstacles in Junior Chamber International's participation in fulfilling the rights of persons with disabilities in Samarinda City. This type of research is a qualitative descriptive study. Data collection techniques are carried out using library research and field research and using observation, interviews, and documentation methods. The data analysis used is an interactive data analysis model. The results of this research showed that the participation of Junior Chamber International (JCI) Indonesia, East Kalimantan Province in fulfilling the rights of persons with disabilities was held through the personal form for the Walk For Autism program and support form is carried out by establishing dialogue, communication and partnerships with the government and providing suggestions regarding the issuance of SIM D for motorbike disabilities.Keywords: Participation, People With Disabilities